Pacific spaces translations and transmutations - Engels-Schwarzpaul, A.-Chr (Pacific perspectives. Studies of the European society for oceanists, 2023)
"Delving into Pacific spaces from a variety of disciplinary perspectives and interpretations, this book looks at how the anthropological and architectural can be connected. The contributors to this book - architectural practitioners, architectural and spatial design theorists, anthropologists and historians - show not only how new theoretical perspectives can arise out of comparing aspects specific to one discipline with their equivalents of another, but also demonstrate how a space of emergence is created for something that goes beyond both, enhancing both fields of potentialities"--